Optimizing the Performance of Bhabinkamtibmas in Batang Police Resort Through the Use of BOS (Binmas Online System) V-2 Application to Realize Public Safety - Nugroho, Ade (Advances in Police Science Research Journal, 2024)
The increasing criminal activities in Batang Regency have become a problem and caused unrest among the people of Batang. The Indonesian National Police (Polri) must take preventive measures through prevention activities carried out by the Bhabinkamtibmas (the police officer assigned to maintain public order and security at the community level) of the Batang Police. This study aims to identify the performance of Bhabinkamtibmas of the Batang Police through the application of BOS (Binmas Online System) V-2 to realize public order and security (kamtibmas). The research was conducted in the jurisdiction of the Batang Police in Central Java. This study used a qualitative approach and field research methods. Data collection was done by conducting interviews, observations, and document studies. The data analysis techniques used were data collection, data reduction, data presentation, and drawing conclusions. This study used conceptual literature including the concepts of optimization, performance, Bhabinkamtibmas, BOS (Binmas Online System) V-2 application, kamtibmas concept, management theory, motivation theory, and SWOT theory. The factual condition in this study is the suboptimal performance of Bhabinkamtibmas of the Batang Police through the application of BOS (Binmas Online System) V-2 to realize public order and security (kamtibmas). In carrying out their duties as Bhabinkamtibmas, their performance is influenced by internal and external factors. Internal factors include a lack of personnel quantity and quality, lack of application development, and a lack of motivation. Meanwhile, external factors include coordination and cooperation with related functions and the community to support the implementation of Bhabinkamtibmas performance.